2020
DOI: 10.1515/gj-2020-0003
|View full text |Cite
|
Sign up to set email alerts
|

Put Dialectics into the Machine: Protection against Automatic-decision-making through a Deeper Understanding of Contestability by Design

Abstract: This paper endorses the idea that the right to contest provided for by art. 22, § 3 GDPR, actually is the apex of a progressive set of tools the data subject has at his disposal to cope with automatic decisions and it should work as an architectural principle to create contestable systems. But in order to achieve that important role, it cannot be reduce to the right of human intervention, also provided for by art.22, § 3, nor to a generic opposition to the outcome of the automatic processing. Thus, drawing fro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
13
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(16 citation statements)
references
References 51 publications
0
13
0
Order By: Relevance
“…A growing number of scholars argue for contestability of AI systems in general, and in automated decision-making specifically (Almada, 2019;Hirsch et al, 2017;Sarra, 2020;Vaccaro et al, 2019). Hirsch et al (2017) describe contestability as "humans challenging machine predictions".…”
Section: Contestability In Automated Decision-makingmentioning
confidence: 99%
See 1 more Smart Citation
“…A growing number of scholars argue for contestability of AI systems in general, and in automated decision-making specifically (Almada, 2019;Hirsch et al, 2017;Sarra, 2020;Vaccaro et al, 2019). Hirsch et al (2017) describe contestability as "humans challenging machine predictions".…”
Section: Contestability In Automated Decision-makingmentioning
confidence: 99%
“…A small but growing body of research explores the concept of contestable AI (Almada, 2019;Henin & Le Métayer, 2021;Hirsch et al, 2017;Lyons et al, 2021;Sarra, 2020;Vaccaro et al, 2019Vaccaro et al, , 2021. However, although many do make practical recommendations, very little of this research is presented in a format readily usable in design practice.…”
Section: Introductionmentioning
confidence: 99%
“…In recent research interpreting Article 22 (3), it is suggested that the ability to contest an outcome will be aided by algorithmic systems being designed to support contestability [5,8,55]. There is acknowledgment that not just the final decision should be rendered contestable, but the entire decision-making process [8].…”
Section: 22mentioning
confidence: 99%
“…In our view, contestability is a broader concept than recourse and appeal as described by Venkatasubramanian and Alfano [64]. Beyond the need for an explanation, contestability requires avenues through which decision subjects can elect to contest a decision [5], and processes that could be used to review algorithmic decisions [5,39,52,55,59,66].…”
Section: Recoursementioning
confidence: 99%
See 1 more Smart Citation